Analysis of the Influence of the Tourism Sector on Regional Original Income in Batu City - Candraningtyas, Callista Vania; Wijaya, Riko Setya; Perdana, Putra (PT Inovasi Pratama Internasional, 2025)
This study aims to determine the extent of influence of the number of tourists, hotel occupancy rates, and the number of restaurants on local revenue in Batu City for the period 2011-2023. The data used in this study were secondary data obtained using a quantitative approach. The data are in the form of Time Series data on the number of tourist visits, hotel occupancy rates, number of restaurants, and local revenue in Batu City. Data were processed using SPSS 25 with multiple linear regression analysis. Based on the results of the study, it can be concluded that the number of tourists, hotel occupancy rates, and number of restaurants have a significant effect on local revenue in Batu City. Partially or individually, the number of tourists has a significant effect, the hotel occupancy rate has a significant negative effect, and the number of restaurants has no significant effect on local revenue in Batu City for the period 2011-2023